Cash flow analysis using coso enterprise risk management (erm) framework on fuel procurement strategy for a sustainable operation, a case study of an Indonesian ipp company - Mutiara, Febrianisa; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2018)
Abstract--- An Indonesian IPP located in Bekasi expanded their power capacity by building a coal fired power plant (CFPP) 2x140MW in 2013. The expansion sums up total installed capacity into 1144MW by 2016 which predominantly using gas fuel operated since 1993. Having coal fuel into their portfolio, this exposes Company to volatile nature of Indonesian coal price. This risks cash flow management of the company including possibility of declining business growth due to future business environment. Short of cash flow is dangerous to not only limit decision making alternative ability related to fuel purchase but also increasing risks of Company sustainability over plant 20 years projected operational period as per COSO Enterprise Risk Management (ERM). Multiple scenarios are randomly simulated assumption to project cash flow and its relevant consequences when repayment of senior note due in 2026. Looking from its historical performance, scenario analysis is plotted using Monte Carlo random simulation on possible end of year cash and cash equivalent outcomes. In mitigating this potential problem, research is going to analyze how COSO enterprise risk management framework mitigates possible cash shortcomings. In conclusion, research recommends an cross divisions contribution within company in developing criteria and technical terms & condition that is jointly real-time monitored for immediate response.Keywords: cash flow analysis; decision making; Monte Carlo random simulation; multiple variables; COSO Enterprise Risk Management